Study of the secondary metabolism of phytopathogenic fungi as a source of compounds with antibiotic activity. - Cotán-García, Ana; Izquierdo-Bueno R, Inmaculada; Pinedo-Rivilla, Cristina (Biosaia: Revista de los másteres de Biotecnología Sanitaria y Biotecnología Ambiental, Industrial y Alimentaria, 2023)
Eutypa lata is a phytopathogenic fungus responsible for a "Grapevine Trunk Disease" commonly called "eutypiosis" or "eutypa dieback" which affects several agricultural crops. Its secondary metabolism has been studied in order to find the main toxins that cause the symptoms of the disease, and to learn how to control its production. One of the most phytophatogenic toxins is Eutypine, a hydroxybenzaldehyde, among several acetylenic derivatives related with it. Syccaine is one of them and exhibits antimicrobial activity against Aerobacter aerogenes and a variety of Gram-positive bacteria, and few fungi. That is why, in this study, we enviosioned the study of the secondary metabolism of E. lata as a producer of natural acetylenic compounds with antimicrobial activity to give response to the worlwide problem posed by the shortage of new antibiotics development. Throught OSMAC (One Strain Many Compounds) approach, two strains of the fungus, E. lata 355 y E. lata 311, were grown using different cultivation conditions like culture media composition, aeration, type of culture flask or incubation time. The extract obtained from the extraction with ethyl acetate of the culture media, was tested against Escherichia coli, Staphylococcus aureus and Klebsiella pneumoniae using the broth dilution method. Then, the extracts with antibiotical activity were purified in order to obtain pure compounds to find which compound are responsible for the antibiotical activity. The preliminary results of the research have indicated that OSMAC approach estimulates the production of compounds with antibiotic activity in some of the culture conditions tested.